ANALISIS FAKTOR YANG MEMPENGARUHI KEINGINAN LANSIA MENGIKUTI POSYANDU DI DESA PASANG LELA KABUPATEN LABUHAN BATU UTARA DENGAN KOEFISIEN KONTINGENSI - Novrika Silalahi; Usaha Tarigan; Ade Afriani (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
This research aims to determine the implementation of government policies regarding the wishes of the elderly in attending the monthly health check up for the elderly in the village of Pasang Lela, North Labuhanbatu Regency. This type of research is a descriptive quantitative study with the research design used is a cross-sectional study. Samples of the research is 71 samples taken using accidental sampling technique. Data analysis using chi-square test. The results of the chi-square test show that there is a significant influence between knowledge, family support, health care services, distance from home in attending the monthly health check up for the elderly in Pasang Lela village with p-value of knowledge is 0,019, p-value of family support is 0,00, p-value of health care service is 0,005, and p-value of distance from home is 0,005. And result of contingency coefficient, family support is the biggest factor of influence elderly’s desire to join posyandu in Pasang Lela village.